Comparing the pharmacokinetics and organ/tissue distribution of anti-methicillin-resistant Staphylococcus aureus agents using a rat model of sepsis. (3rd June 2022) - Kobuchi, Shinji; Kanda, Naoya; Okumi, Taichi; Kano, Yuma; Tachi, Himawari; Ito, Yukako; Sakaeda, Toshiyuki
Abstract: Sepsis is a major cause of death, and sepsis-derived physiological changes complicate the understanding of drug distribution in organs/tissues, which determines the efficacy and toxicity of antimicrobial agents. In this study, we evaluated and compared the pharmacokinetics of methicillin-resistant Staphylococcus aureus treatment agents in sepsis with that of vancomycin, arbekacin, linezolid, and daptomycin. Rat models of sepsis were prepared using caecal ligation puncture. The pharmacokinetics of vancomycin, arbekacin, linezolid, and daptomycin were evaluated using their drug concentration profiles in plasma, kidneys, liver, lungs, skin, and muscles after intravenous administration in normal and septic rats. The kidney/plasma concentration ratio was higher in septic rats than in normal rats for vancomycin, arbekacin, and daptomycin but not for linezolid. The increase in the kidney/plasma concentration ratio for vancomycin was time-dependent, indicating an association between sepsis and stasis of vancomycin in the kidneys. In contrast, the distribution of linezolid from the blood to the organs/tissues in septic rats was comparable to that in normal rats. Sepsis-induced nephrotoxicity results in the stasis of vancomycin in the kidney, suggesting that this exacerbates proximal tubular epithelial cell injury. No dose modification of linezolid may be required for patients with sepsis.